Afro-Dominican voices: Identity, Justice, and Revenge in Three Trans* and Non-binary Poems - Hernández-Gutiérrez, Antony (2025)
This article aims to analyze the decolonial, anti-racist, and anti-cis-sexist struggles undertaken by trans* and non binary Afro-Dominican voices as a mechanism of denunciation in their poems “Quiero otra justicia” by Drullard (2021) and “a sudores” and “Quiero venganza” by seba (2022). This analysis is based on the study of poetic composition, literary and structural figures, as well as the use of language, which emphasize how violence is represented by the lyrical voices. Additionally, it examines the (self-)representation of identity constructed in the poems and the reaffirmation of trans* and non-binary existence as a resource of resistance against racist, colonial, capitalist, and cisheteropatriarchal power structures. A descriptive and hermeneutical methodology with an intersectional approach is employed for this purpose. The text concludes that the struggles undertaken by the authors share a common foundation in the coloniality of power and racism, intersecting with other categories related to sex-gender identity and socioeconomic status.